Implementação de um sistema de avaliação web aplicando técnicas de gamificação para utilização em ambiente acadêmico - FREIRE, Matheus Ferreira (2019)
Nowadays, it has been very common to use educational software during the learning process. This kind of technology can be used as a tool to help the professors, as well as motivating the students when they are acquiring knowledge. The use of gamification mechanics also contributes to the motivation of students from the primary school to the University. Gamification has been very utilized during the last few years in the fields of business, health and education. These two facts by themselves, motivated this work which consists in the development of a web software that creates and manages online tests. The software called SAAW will be initially applied in the “Universidade Federal do Pará”, in the computer science major. This tool storages questions from many fields of knowledge and applies online real and simulated tests. There is a registration system where the users, including both professors and students, can register by putting on their data in order to have access to all the functionalities the platform provides. The professor is able to add questions to the platform, create tests and apply these tests as he wishes. He will not need to grade these tests because the platform will do that automatically. The students are able to make simulated tests to train their skills and make real tests whenever the professor turn them available in the platform. The access to the application was tested using the WebPageTest tool. During the analysis, tests were made with Quizizz and facebook in order to compare their performance with the platform. Simultaneous access tests were made and they confirmed the good performance of the platform.